The Effects of Risk Management System on Financial Performance of Commercial Banks in Rwanda: A Case of Cogebanque Ltd. - Hitimana, Mireille; Kule, Julius Warren; Mbabazize, Peter Mbabazi (American Journal of Trade and Policy, 2016)
This research study entitled an Assessment of the Effect of Risk Management System on Financial Performance of Commercial Banks in Rwanda aimed at assessing risk factors that performance of commercial banks like credit risk, embezzlement, theft and among others. Three specific objectives were formulated namely; to analyze the effect of directive control system on Financial Performance of Cogebanque Ltd; to establish the effect of preventive control system on Financial Performance of Cogebanque Ltd; to examine the effect of detective control system on Financial Performance of Cogebanque Ltd. The study examined risk management system and financial performances in Cogebanque Ltd located in Kigali City for a period of four years from 2011-2014. The study used descriptive design. A sample size of 40 staff of Cogebanque Ltd, participated in the study. SPSS software (version 22) was used to process the data and analysis were made by use of frequency/percentages, mean and standard deviation. The relationship between the variables was established by use of Pearsons correlation.  The study established that different risk management systems which consist of directive control system, preventive control system and detective control system. The study revealed that risk management system has improved Cogebanque bank’s return on investment, profitability, liquidity, return asset and return on equity and loan returns by 72.7%.
Keywords: Risk Management; Internal Control Systems; Financial Performance; Commercial Banks; Rwanda